Recent Advances and Future Prospects in Knowledge, Information and Creativity Support Systems Selected Revised Papers from the Tenth International Conference on Knowledge, Information and Creativity Support Systems (KICSS 2015), 12-14 November 2015, Phuket, Thailand - Theeramunkong, Thanaruk; Skulimowski, Andrzej M.J.; Yuizono, Takaya; Kunifuji, Susumu; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2018)
This book includes carefully selected papers presented at the 10th International Conference on Knowledge, Information and Creativity Support Systems (KICCS 2015), which was held in Phuket, Thailand, on November 12-14, 2015. Most of the papers are extended versions with the latest results added, representing virtually all topics covered by the conference. The KICCS 2015 focus theme, "Looking into the Future of Creativity and Decision Support Systems", highlighted the field's growing complexity and called for deeper, insightful discussions about the future, complemented with an exposition of current developments that have proven their value and usefulness. As such, the book addresses topics concerning future-oriented fields of research, such as anticipatory networks and systems; foresight support systems; and relevant newly emerging applications, exemplified by autonomous creative systems. It also focuses on cognitive and collaborative aspects of creativity.
Detecting TV Program Highlight Scenes Using Twitter Data Classified by Twitter User Behavior -- BrainTranscending: A Hybrid Divergent Thinking Method that Exploits Creator Blind Spots -- Open Data Integration for Lanna Cultural Heritage e-Museums -- An Expert System Using Ontology as Knowledge Base for Personalized Rice Cultivation Suggestion -- Designing a social innovation based knowledge support system: A preliminary guideline -- A Study of Cost, Revenue, and Profit Efficiency of Commercial Banks in Cambodia using DEA Approach -- Competition Boosts Innovativeness: the Case of CMS Evolution -- Modeling Traffic Accidents Occurrences Based on Land Use and Road Factors Using Geographically Weighted Regression Models -- A Model-based Method for Modeling and Verifying Event-Based Aspect-Oriented Applications -- A Retrospective on Constructing a Personal Narrative on Agile Development.
Keywords: Computational intelligence; Artificial intelligence; Computational Intelligence; Artificial Intelligence